Behavioral syndromes vary among geographically distinct populations in a reptile. (19th December 2018) - Michelangeli, Marcus; Chapple, David G; Goulet, Celine T; Bertram, Michael G; Wong, Bob B M
Abstract: A key goal in the study of animal personalities is to determine their adaptive potential and importance for behavioral evolution. Behavioral syndromes are evolutionarily intriguing because they suggest that an adaptive change in one behavior requires a concomitant shift in another. Within species, behavioral syndromes might be evolutionarily constrained by intrinsic mechanisms that restrict behaviors from evolving independently. Alternatively, behavioral correlations might easily be decoupled over short evolutionary time scales due to variation in selective pressures between environments. In this regard, comparative studies that explore differences in diverse aspects of personality between geographically distinct populations can provide valuable insights into the evolutionary processes acting on different behavioral tendencies. Accordingly, we investigated how behavioral types and behavioral syndromes differed across four geographically distinct populations of the delicate skink, Lampropholis delicata. We found strong evidence of mean trait-level variation in activity, exploration, and boldness across populations, suggesting adaptation to local environmental conditions. Similarly, we found that within-population correlations involving boldness varied substantially between populations. However, we did find a consistent within- and among-population correlation between activity and exploration, suggesting that this behavioral syndrome is relatively stable and could explain behavioral divergence in activity and exploration between populations. We suggest that there may be thermal physiological mechanisms that could be limiting the adaptive potential of an activity-exploration correlation in the delicate skink. Broadly, we argue that some behavioral correlations may be more adaptive than others, and that this should be more regularly considered within the animal personality framework. Abstract : Animals have personalities which have important consequences for individual survival and population dynamics. We compared personality traits between 4 populations of a lizard to understand how different personalities might evolve. Populations expressed markedly diverse personalities, but we did find in all populations that lizards which were most active were also the most explorative. Our results suggest that some personalities are mostly shaped by environmental factors, whereas others are mediated by internal constraints like physiology.